Akuntansi Pesantren Di Pondok Pesantren Darul Qur'an Wal Hadits Toili - Fitriani, Fitriani (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2023)
The purpose of the research is to find out that the preparation of financial reports for the Darul Qur'an Wal Hadith Islamic Boarding School is in accordance with applicable standards. In this study the type of data used is qualitative data. Data collection methods used in this study were interviews, observation, documentation. The data analysis technique in this study is to use the Islamic boarding school accounting method. The results of this study indicate that the recording of financial reports at the Darul Qur'an Wal Hadith Islamic Boarding School is recorded modestly, the reason for recording is done soberly is because the management of the Islamic Boarding School does not understand how to prepare financial reports in accordance with correct accounting standards and also limited knowledge so that the preparation of financial reports accordance with the applicable accounting standards have not yet been implemented. Keywords : Islamic boarding school accounting